ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL MENGGUNAKAN MODEL INDEKS TUNGGAL (Studi pada Saham LQ45 di Bursa Efek Indonesia Periode Maret 2016-Februari 2018) - KURNIA DWI CHAIRUNNISA ; Toto Rahardjo, SE., MS. (Manajemen FEB - UB, 2018)
The aim of this study was to apply single index model in the formation of the optimal portfolio of stocks that are continuously going in the LQ45 Index category in the selected period, February 2016 – February 2018. This study was an empirical study. The data in this research is secondary data obtained from BEI, Yahoo Finance, and BI. The technique used for sampling is purposive sampling. The criteria of samples were stocks of companies listed and actively traded on the Indonesia Stock Exchange consistently entering into the LQ45 index in period 2016- 2018 and was selected 25 stocks to be a sample. The analysis technique used is descriptive analysis and processing of data using Microsoft Excel 2013. Based on the results of the analysis, of the 26 members of samples, a combination of 7 stocks that can form an optimal portfolio with proportion: Adaro Energy Tbk (ADRO) 18,54%, United Tractors Tbk. (UNTR) 27,54%, Bank Tabungan Negara Tbk (BBTN) 13,44%, Bank Central Asia Tbk (BBCA) 26,97%, Bank Negara Indonesia Tbk (BBNI) 11,95%, Gudang Garam Tbk (GGRM) 0,98% dan Unilever Indonesia Tbk. (UNVR) 0,59%. Expexted return of the optimal portfolio combination is 3,18% with a risk of 0,067%. Keywords: single index model, optimal portfolio, lq45 index